Synthesis of nanoporous carbon from brewer waste by hydrothermal carbonization assisted chemical activation for carbamazepine adsorption - Naruemon Apinyakul; Sirayu Chanpee; Napat Kaewtrakulchai; Narathon Khemasiri; Apiluck Eiad‐ua; Pornsawan Assawasaengrat (Case Studies in Chemical and Environmental Engineering, 2024)
Nanoporous carbon (NPC) has gained significant attention in wastewater treatment due to its effectiveness. The adsorption process, known for its simplicity, stability, and cost-effectiveness, is widely recognized as an efficient method for removing carbamazepine (CBZ) residues accumulate in the environment. However, the application of NPC is often hindered by challenges in the regeneration process after use, as well as issues related to large surface area, pore size, and functional groups. Fortunately, the samples in this study not only maintained their adsorption efficiency but also demonstrated the ability to be regenerated multiple times. Herein brewery waste was subjected to hydrothermal treatment at 200 °C for 1 h and followed by KOH and NaCl activation with different KOH:NaCl (w/w) ratios of 5:0, 4:1, 3:2, 1:1, 2:3, 1:4, and 0:5 to optimize the properties of malt husk derived nanoporous carbon (NPC). The optimal condition KOH:NaCl ratio of 1:1 had a maximum specific surface area of 906 m2/g with a total pore volume of 0.252 . According to the adsorption test, the CBZ adsorption isotherm was well-fitted to the Langmuir model (R2 = 0.976) kinetic data were consistent with the pseudo-second-order model (R2 = 0.995). This suggests that the adsorption mechanism involves monolayer adsorption and chemisorption interaction. The Gibbs free energy and enthalpy of CBZ adsorption by NPC were found to be spontaneous and endothermic. The regeneration test revealed a 95.35% decrease in the adsorption capacity of NPC after 5 repeated cycles. Consequently, the study suggests a potential application of nanoporous carbon from MH as an alternative adsorbent for removing carbamazepine in wastewater.
Keywords: Adsorption and biosorption for pollutant removal; Nanomaterials for catalytic reactions; Covalent Organic Framework Applications